Treatment of infectious aortic disease with bovine pericardial tube grafts. (1st February 2021) - Kreibich, Maximilian; Siepe, Matthias; Berger, Tim; Pingpoh, Clarence; Puiu, Paul; Morlock, Julia; Walter, Tim; Kondov, Stoyan; Beyersdorf, Friedhelm; Rylski, Bartosz; Czerny, Martin
Abstract: OBJECTIVES: Our aim was to evaluate the mid-term outcomes of bovine pericardial tube graft repair for infectious aortic disease in any aortic segment. METHODS: Between May 2015 and July 2020, 45 patients were treated for infectious aortic disease of the native ( n  = 9) aorta or after (endo-)graft ( n  = 36) implantation with bovine pericardial tube grafts. Clinical, infectious details, outcomes and follow-up data were evaluated. RESULTS: All aortic segments underwent pericardial tube graft or bifurcational replacement: the aortic root ( n  = 12, 27%), ascending aorta ( n  = 18, 40%), aortic arch ( n  = 7, 16%), descending aorta ( n  = 5, 11%), thoraco-abdominal aorta ( n  = 6, 13%) and abdominal aorta ( n  = 18, 40%) including the iliac arteries ( n  = 14, 31%). Organ fistulation ( n  = 15, 33%) was the most common underlying pathology. Seven patients (16%) expired in-hospital secondary to ongoing sepsis ( n  = 5, 11%), respiratory failure ( n  = 1, 2%) and unknown cause ( n  = 1, 2%). A fungal infection was predictive for in-hospital mortality ( P  = 0.026, odds ratio: 19.470). After a median follow-up of 11 [first quartile: 2, third quartile 26] months, 9 additional patients (20%) expired and 1 patient developed a postoperative spondylodiscitis at the level of the aortic tube graft. Hence, freedom from proven aortic graft re-infection was 98%. CONCLUSIONS: Orthotopic aortic reconstruction using bovine pericardial tube grafts to treat infectious aortic disease is possible in any aortic segment. Organ fistulation is a frequently observed disease mechanism requiring concomitant treatment. Granted, the early attrition rate is substantial, but after the initial period, both survival and freedom from re-infection appear encouraging.